Islamic Consumption in the Digital Era: A Conceptual Analysis of the Qur’an, Hadith, DSN-MUI Fatwas, and Its Implications for Muslim Consumer Behavior - Shohwatul Islamiah; Muhammad Irwan Padli Nasution; Muhammad Habibi Siregar (Yayasan Darussalam Bengkulu, 2026)
Background: This article examines Islamic consumption as articulated in the Qur'an, hadith, scholarly thought, and DSN-MUI fatwas, and assesses its implications for Muslim consumer behavior in the digital era. Digital consumption has widened access to halal products while creating new risks, including impulsive purchasing, manipulative promotion, incomplete product information, digital payment instruments, buy-now-pay-later services, live shopping, and unverified halal claims. Method: The study employs a qualitative library-research design with normative, thematic, and content-analytical approaches. Primary sources comprise relevant Qur'anic verses, hadith, and DSN-MUI Fatwa No. 146/DSN-MUI/XII/2021 on Online Shops Based on Sharia Principles. Secondary sources include scholarly articles, regulations, and official reports published since 2020. Results: The analysis identifies five foundations of Islamic consumption: halal, thayyib, balance, maslahah, and transactional justice. In digital markets, these principles require consumers to assess not only halal certification but also contractual transparency, seller credibility, payment mechanisms, data security, consumer reviews, and the social consequences of purchasing decisions. Conclusion: The article develops a maqashid sharia-based framework that treats digital consumption as an economic activity governed by moral and spiritual responsibility.